The Influence of Financial Ratios on The Profitability of Conventional Commercial Banks Listed on The Indonesia Stock Exchange - Jessen, Jessen; Purnama Yanti Purba; Davin Kendrew; Jhon Raphael Saragih (Cita konsultindo, 2025)
This paper aims to determine the effect of CAR, NPL, BOPO, and LDR on the ROA of conventional commercial banks listed on the IDX in the period 2019–2023. This type of research is a descriptive analysis, using 27 banks that passed the criteria test and producing a total sample of 135 samples. The tests used in this paper include multiple linear regression analysis, a normality test, a multicollinearity test, an autocorrelation test, a heteroscedasticity test, a coefficient of determination, an F test along with a t test. The results show that CAR does not affect ROA, NPL does not affect ROA, BOPO does affect ROA, and LDR does not affect ROA. At the same time, CAR, NPL, BOPO, and LDR all affect ROA.